A Combined Path-SITOREM Analysis to Investigate Effective Islamic Instructional Strategies through Transformational Leaderships, Motivation, and Cooperative Learning Method - Andi Hermawan (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This study will develop strategies for increasing the effectiveness of teaching in Islamic Religious Education (IRE) in private vocational schools in Bogor Regency through an analysis of the influence of transformational leadership, models of cooperative learning, and motivation to learn. A quantitative approach was used whereby questionnaires were distributed to a sample of 168 from a total population of 289 teachers as calculated through Slovin's formula. The data analyses include the use of path analysis for testing relationships among variables and the SITOREM method for establishing indicators prioritization for intervention. Results indicated that transformational leadership, cooperative learning models, and learning motivation contributed significantly to effective learning. Cooperative learning, motivation, and leadership show the strongest direct effect in decreasing order. Learning motivation also served as the mediator of leadership and cooperative learning influences towards learning results. Based on the performed SITOREM analyses, indicative categories such as promotive interaction and inspirational motivation that appeared to still require further improvement required priority and serious attention, but those, like individual accountability and task orientation, that have been high should just be preserved. These findings make possible a strategic view of developing the quality of IRE instruction with regard to weaknesses and strengths, based on leadership, cooperative learning, and motivational practices. In conclusion, the study points to the significance of integrating transformational leadership, cooperative learning strategy, and intrinsic-extrinsic motivation in driving effective IRE teaching outcomes. The results give recommendations that are useful for educators, school administrators, and policymakers in the improvement of the quality of education. Keywords: transformational leadership, cooperative learning, motivation, path analysis, SITOREM analysis.